A Comparative Analysis of Financial Management and Profitability between Digital Ecosystem-Based Retail Companies and Conventional Retail Companies Listed on the Indonesia Stock Exchange (IDX) - Siti Athirah Asmarani; Syahra Darajat Salsabila; Nurhalima; Muchriana Muchran (www.amertainstitute.com, 2026)
The development of digital ecosystems has transformed the competitive landscape of the retail sector in Indonesia, raising questions about which business model excels in financial management and profitability. This study aims to analyze and compare the financial management performance and profitability levels of digital ecosystem-based retail companies versus conventional retail companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. A comparative quantitative approach using purposive sampling was employed, resulting in a sample of six companies (three digital ecosystem issuers: BELI, BUKA, GOTO; and three conventional issuers: AMRT, LPPF, HERO), yielding 18 panel data observations. Financial management was measured via cash turnover, inventory turnover, and the operating expense ratio (BOPO), while profitability was measured via Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Data were analyzed using the Independent Sample T-test following the Kolmogorov-Smirnov normality test and Levene’s homogeneity test. The results indicate significant differences (Sig. 0.000 < 0.05) across all tested indicators. Digital retailers outperformed in cash and inventory turnover speeds but lagged significantly in operating cost efficiency (average BOPO of 118.60% compared to 92.10% for conventional retailers). Regarding profitability, conventional retailers consistently recorded positive ROA, ROE, and NPM, whereas digital retailers remained in a net loss position. These findings indicate that the working capital efficiency advantage of digital ecosystems has not yet translated into net profitability, consistent with a U-shaped relationship pattern observed during the early stages of digital transformation.